INTEGRASI ESG DALAM SISTEM PENGENDALIAN MANAJEMEN PERBANKAN SYARIAH: TINJAUAN LITERATUR 2021 - 2025 - Novita Fitrah Ramadhani3; Intan Mutiara; Monica Dwi Tara (Journal of Islamic Economics and Finance, 2025)
This article discusses the integration of ESG(Environmental, Social, and Governance) in the management control systemof Islamic banking. Islamic banking in Indonesiaintegrates the core values of Islamic economics throughout its services. Thismainly involves the prohibition of interest and other financial transactions that are consideredcontrary to Islamic principles. In addition, Islamic banking also hasa commitment to help the community and the environment. Therefore,ESG principles are naturally aligned with whatIslamic banking aims to achieve.This research uses the Systematic Literature Review(SLR) method with the PRISMA (Preferred Reporting Items forSystematic Reviews and Meta-Analyses) approach. The data population of this study consistsof 20 journals from 2021-2025 that focus on ESG in the management controlsystem. The results of this study show thatenvironmental, social, and governance (ESG) management practices have become an important element inmanagement control systems, particularly in the Islamic banking sector, over the lastdecade. From 2021 to 2024, there was a significant increasein publications discussing ESG in the context of Islamic banking, whichsuggests that ESG is in line with shariah maqāṣid principles and cansupport sustainable financial performance.